2023
DOI: 10.32604/cmc.2023.034209
|View full text |Cite
|
Sign up to set email alerts
|

View Types and Visual Communication Cues for Remote Collaboration

Abstract: Over the last several years, remote collaboration has been getting more attention in the research community because of the COVID-19 pandemic. In previous studies, researchers have investigated the effect of adding visual communication cues or shared views in collaboration, but there has not been any previous study exploring the influence between them. In this paper, we investigate the influence of view types on the use of visual communication cues. We compared the use of the three visual cues (hand gesture, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recently, Wang et al [23] proposed a SAR remote collaboration platform providing AAS and gesture cues, and the results showed AAS cues are more bene cial to remote users naturally expressing instructions. Kim et al [39] developed an AR remote collaborative platform to explore the in uence of three different visual cues (e.g., gestures, pointer, AAS), and the results showed that AAS, particularly, the combination of gestures and AAS, requires less cognitive effort, provides better communication cues, and increases the feeling of co-presence in the case of the dependent view. Most center attention on easily and intuitively expressing cues and the use of AAS to augment the on-site setting, such as sketches, pointers, and pre-designed visual cues (e.g., arrows), effectively enhancing remote collaborative tasks[8, 45,46].…”
Section: Sharing Aas Cuesmentioning
confidence: 99%
“…Recently, Wang et al [23] proposed a SAR remote collaboration platform providing AAS and gesture cues, and the results showed AAS cues are more bene cial to remote users naturally expressing instructions. Kim et al [39] developed an AR remote collaborative platform to explore the in uence of three different visual cues (e.g., gestures, pointer, AAS), and the results showed that AAS, particularly, the combination of gestures and AAS, requires less cognitive effort, provides better communication cues, and increases the feeling of co-presence in the case of the dependent view. Most center attention on easily and intuitively expressing cues and the use of AAS to augment the on-site setting, such as sketches, pointers, and pre-designed visual cues (e.g., arrows), effectively enhancing remote collaborative tasks[8, 45,46].…”
Section: Sharing Aas Cuesmentioning
confidence: 99%